Opposite Effects of Mineral Dust Nonsphericity and Size on Dust‐Induced Snow Albedo Reduction. Issue 12 (23rd June 2022) - Shi, Tenglong; He, Cenlin; Zhang, Daizhou; Zhang, Xuelei; Niu, Xiaoying; Xing, Yuxuan; Chen, Yang; Cui, Jiecan; Pu, Wei; Wang, Xin
Abstract: We quantified the combined effects of mineral dust nonsphericity and size on snow albedo reduction using the MOPSMAP (Modeled optical properties of ensembles of aerosol particles) package and SAMDS (Spectral Albedo Model for Dirty Snow) with the consideration of dust from Sahara, Greenland, San Juan Mountains, and Tibetan Plateau. Results indicate that the dust‐induced albedo reduction decreases by up to 30% as the effective radii of dust particles increase in 1–5 μm. Nonspherical dust enhances snow albedo reduction relative to spherical dust by up to 20%. Stronger enhancements are obtained for higher dust concentration and larger dust size. Furthermore, the dust nonsphericity‐induced enhancement of snow albedo reduction is more pronounced for more‐absorptive dust. Finally, we develop a new parameterization for quantifying the dependence of snow albedo reduction on dust nonsphericity and size, and provide a convenient way for assessing the climate impacts of dust in snow. Plain Language Summary: Mineral dust particles are a major type of light‐absorbing aerosols in the atmosphere, with the absorptivity closely dependent on their shape and size. Previous studies have confirmed that dust particles deposited on snow surface varied largely in size and shape, and caused the reduction of snow albedo worldwide. In this study, we quantified the effects of dust size and nonsphericity on the induced snow albedo reduction. Results show that small and nonspherical dust particles induce large snow albedo reduction, in comparison with large and spherical dust particles. We further develop a parameterization for the dust size and nonsphericity effects for application in climate models. Key Points: Mineral dust‐induced snow albedo reductions rapidly decrease as dust size increases Nonspherical dust causes larger snow albedo reduction than spherical dust by up to 20% A new parameterization is developed to improve the estimate of snow albedo reduction with dust size and nonsphericity